Description of inclusive meson spectra in e+e- annihilation reactions by a quark cascade model - Batista, M. [UNESP]; Bellandi, J.; Covolan, R. J M (Oxford University Press (OUP), 1997)
We present a model to describe inclusive meson production in e+e- reactions based on a quark cascade approach whose formulation is put in terms of diffusion equations for three quark flavors (u, d, s). These equations are solved by using a formalism previously developed for the problem of the electromagnetic cascade generated in the atmosphere by cosmicray interactions. The obtained solutions are given in terms of a combination of power-law functions whose profiles are adequate to describe the characteristics observed in the inclusive spectrum of mesons.